Faktor-Faktor Kejadian Stunting pada Anak Usia 12-23 Bulan di Kecamatan Kedondong Kabupaten Pesawaran - Chintia Margareta; Fitri Ekasari; Nurhalina Sari (Jurnal Kesehatan Amanah, 2026)
Background: Stunting threatens the future of the nation’s next generation, until 2022 the National stunting incidence rate (21,6%) is still high including in Lampung Province (15,2%) and Pesawaran Regency ranks first for children who experience stunting where the incidence of stunting increased from the previous year to 25,4%. Based on the data of Public Health Office of Pesawaran Regency the highest incidence of stunting is Public Health Center of Kedondong with a total of 124 children out of a total of 584 stunted children. Research method: analytic survey research with a cross sectional approach. The population of the research is all mothers and children aged 12-23 months, while the number of samples from 12 villages obtained as many as 110 respondents. Sampling technique using is proportional simple random sampling and the data obtained in the analysis using is logistic regression. Research results: maternal height (OR= 9.836, pV=0.001) and IMD (OR=4.326, pV= 0.011) were the most dominant factor associated with the incidence of stunting in Kedondong District Pesawaran Regency in 2023. Special attention needs to be given to pregnant women who have a height <150cm to be able to prioritize nutritional intake in 1000 HPK, starts from the pregnant until the child is 2 years old, especially the high intake of protein and ensure when the child is born must get IMD to avoid risks of stunting and avoid passing on short stature to the next generation.